The Level of Satisfaction Among Patients with Dental Bridges - Astuti, Titis Hadiyanti; Kusumadewi, An-nissa; Pramudita, Seto (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
Dental bridges are one of the treatments for tooth loss cases. Dental profession students at the Faculty of Dentistry of Universitas Padjadjaran (Unpad) conducted their first dental bridge treatment on patients. Evaluating patient satisfaction is essential to measure the success of treatments provided by dental students. This study aims to determine patient satisfaction with the dental bridges treatment provided by dental professional students at the Prosthodontics Polyclinic in terms of chewing, aesthetics and phonetics function, maintenance of the denture, and psychological aspects. This type of research is descriptive cross-sectional. Eighty-two dental bridges users were selected using total sampling at the Prosthodontic Polyclinic from September 2022 to February 2023 out of a total population of 86 users. The inclusion criteria included male or female patients using PFM or full metal dental bridges in the upper or lower jaw, worn for at least seven days to 6 months after definitive cementation, and made a control visit after the insertion of dental bridges. The instrument used was a modified questionnaire called the Patient Denture Assessment (PDA) and an Indonesian version of PDA (PDA-ID), with 12 modified Likert scale questions given online. The results of the study showed that 86,6% of the respondents were satisfied with masticatory function, 97,6% were satisfied with aesthetics and phonetics, 82,9% were satisfied with the maintenance of the denture, and 93,9% were satisfied with the psychological aspects of the use of dental bridges. Most patients were satisfied with dental bridges regarding chewing, aesthetics and phonetics function, denture maintenance, and psychological aspects.